Adult intussusceptions induced by a terminal ileum diverticulum: a case report. Issue 4 (23rd February 2018) - Nakazawa, Nobuhiro; Suzuki, Hideki; Ebara, Gen; Watanabe, Yu; Tsukagoshi, Ritsuko; Ieta, Keisuke; Morohara, Koji; Osawa, Hidenobu; Katayama, Kazuhisa; Yasuda, Yasukuni; Tanaka, Shigehumi; Kuwano, Hiroyuki
Key Clinical Message: We herein report a case of adult intussusceptions induced by a terminal ileum diverticulum. Histological examination confirmed a terminal ileum diverticulum full of feces, and it was considered an infiltrated region. The clinical characteristics of previously reported adult intussusceptions are also discussed, including jejunoileal diverticulum and surgical management. Abstract : We herein report a case of adult intussusceptions induced by a terminal ileum diverticulum. Histological examination confirmed a terminal ileum diverticulum full of feces, and it was considered an infiltrated region. The clinical characteristics of previously reported adult intussusceptions are also discussed, including jejunoileal diverticulum and surgical management.